The Effect Of Anti-Corruption Education And Social Media On The Perception Of Whistleblowing : Case Study Of Students Of Indo Global Mandiri University - Indri Bulan Sari; Rum Hendarmin; Mutiara Kemala Ratu (STIE Amkop Makassar, 2026)
Corruption is a serious problem that hinders national progress and harms state finances. Public participation in whistleblowing is still relatively low, so strategies through education and the use of social media are needed to change this perception. This study aims to analyze the influence of anti-corruption education and social media on students' perceptions of whistleblowing. The research method used a quantitative approach with data collection using a questionnaire. The study population was 55 students of the Accounting Study Program at Indo Global Mandiri University, class of 2022, who had taken the Professional Ethics course. The data analysis technique used multiple linear regression. The results showed that anti-corruption education had a positive and significant effect on perceptions of whistleblowing (sig. 0.001). Social media also had a positive and significant effect on perceptions of whistleblowing (sig. 0.010). Simultaneously, both variables significantly influenced perceptions of whistleblowing, with a calculated F-value of 13.531 (sig. <0.001) and a coefficient of determination of 34.2%. The conclusion of this study is that anti-corruption education and social media play an important role in forming students' positive perceptions of whistleblowing as a form of moral responsibility and part of a culture of integrity.